Optimization of weld strength in indirect resistance welding of AISI 316L wires: A study on the synergistic effects of pulsed current and preheat temperature - Vardanjani , Mehdi Jafari; Araee , Alireza (Archive of Mechanical Engineering, 2026)
This study investigates the enhancement of weld strength in indirect resistance welding of AISI 316L stainless steel wedge wires by systematically evaluating the effects of pulsed current frequency and preheating temperature. A comprehensive Design of Experiments (DOE) approach was employed, incorporating varying pulsation frequencies (0–10 Hz) and preheat temperatures (50–200◦C), while maintaining constant welding current (7 kA) and time (25 cycles). Experimental and numerical analyses were conducted to assess shear-tensile strength and heat-affected zone (HAZ) depth. Results demonstrate that both pulsed current and elevated preheating contribute significantly to improved mechanical performance. Pulsation promoted localized energy concentration, reducingHAZextent and enhancing joint strength, while preheating mitigated thermal gradients and residual stresses, further increasing loadbearing capacity. The combined application of optimized pulsation and preheating parameters proved effective in overcoming loose connections and achieving superior weld integrity, offering a reliable strategy for quality improvement in the resistance welding of fine metallic components.